Perkembangan Supervisi Pendidikan - M. Edi Suharsongko (Jurnal Alasma : Media Informasi dan Komunikasi Ilmiah, 2019)
Supervision has a central position in efforts to foster and develop cooperative activities within an organization. Educational institutions as one form of organization certainly can not escape from supervision activities. In the environment of these educational institutions involved a number of humans who must work together in achieving a goal. Business assessment, coaching, development, and control of educational institutions is certainly can not be separated from the problem of methods and tools and human problems themselves that must be able to realize work effectively. Therefore, in the effort of assessment, coaching, development, and control of educational institutions is very necessary application of educational supervision.Educational supervision has a long his-tory, educational supervision that has actually existed since the existence of humans, even in a simple level and level. Initially educational supervision refers to the supervisory work, although it ultimately boils down to professional help. In the context of the school as an educational organization, supervision is part of the administrative process. Supervision activities complement the administrative functions that exist in the school as the last function, namely the assessment of all activities in achieving goals. Super-vision has a role to optimize the responsibilities of all programs.